2021
DOI: 10.3390/children8110943
|View full text |Cite
|
Sign up to set email alerts
|

The Neurobehavioral Phenotype of School-Aged, Very Prematurely Born Children with No Serious Neurological Sequelae: A Quality of Life Predictor

Abstract: School-aged extremely preterm (EPT) children have multiple specific neurocognitive/behavioral disorders that are often associated with other disorders; this manifests a true neurobehavioral “phenotype” of prematurity. To determine a profile of cognitive/behavioral impairments in a population of school-aged EPT children (7–10 years-old) without major disabilities, a cross-sectional study was conducted in five medical centers. An algorithm distributed the study population according to four WISC-IV subtests, five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A recent study showed that a cluster analysis taking into account the whole cognitive development (including EFs) and a behavior analysis defined three distinct outcome groups in extreme premature children without severe disabilities, providing an informative means for identifying factors related to developmental outcomes. This study showed that QOL deterioration was determined by the severity of the three neurobehavioral “phenotypes” and was also defined by dysexecutive and/or behavioral disorders [ 1 ].…”
Section: Understanding the Neurodevelopment Of Prematurity Requires E...mentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study showed that a cluster analysis taking into account the whole cognitive development (including EFs) and a behavior analysis defined three distinct outcome groups in extreme premature children without severe disabilities, providing an informative means for identifying factors related to developmental outcomes. This study showed that QOL deterioration was determined by the severity of the three neurobehavioral “phenotypes” and was also defined by dysexecutive and/or behavioral disorders [ 1 ].…”
Section: Understanding the Neurodevelopment Of Prematurity Requires E...mentioning
confidence: 99%
“…As well as being a health issue [ 8 , 150 , 151 ], a better understanding of the long-term future of children born prematurely under all these aspects is essential, since it provides parents with scientifically based and reliable information and improves care thanks to the understanding of neurodevelopmental disorders [ 1 ].…”
Section: Perspectives Executive Functions and Analysis Of Neurobehaviormentioning
confidence: 99%
See 3 more Smart Citations